Incidencia de la violencia intrafamiliar y su relación con los traumas de las pacientes que son atendidas en el hospital El Empalme, provincia del Guayas, Distrito 09d15-salud enfermera, año 2013 - Porro Vargas, Luisana Estrella (2015)
Domestic violence has been defined as any relationship, process or condition for which an individual or social group violates the physical, psychological or social integrity to someone else. The importance lies in the final report of the World Health Organization (WHO) on Domestic Violence and Health, the study shows that 30% of women worldwide suffer domestic violence by their partners and the 35% will suffer in the couple or outside it, at some point in their lives. In Ecuador it is estimated that 6 in 10 women have suffered some form of violence, health problems associated with the abuse, appear among the leading causes of illness and death.